Aspects of the quality of accounting in the international context - Sady Mazzioni; Roberto Carlos Klann (Revista Brasileira de Gestão De Negócios, 2018)
Purpose – Analyze how the characteristics of the business environment generates differences in the quality of accounting information in the international context. Design/methodology/approach – Descriptive research with a quantitative approach. Documentation collection in the Thomson Datastream Index Service database in a sample of 1,406 companies located in twelve countries, from 2005 to 2012. Findings – Companies located in countries with lower tax burden, stronger legal environment, greater economic and financial development index, common law legal origin and higher degree of internationalization presented higher averages and significant differences in the aggregate ranking of the quality of accounting information. The type of standard accounting used also influenced the position in the aggregate ranking of the accounting information quality. Originality/value – The interaction of companies with external markets influences the choices of accounting policies. The countries’ environmental characteristics, related to transparency, economic nature, legal and tax environment, lead to various levels of the quality of accounting information reported by companies.